Drawing Inspiration from Developmental Biology for Cardiac Tissue Engineers. Issue 7 (19th May 2021) - Rafatian, Naimeh; Vizely, Katrina; Al Asafen, Hadel; Korolj, Anastasia; Radisic, Milica
Abstract: A sound understanding of developmental biology is part of the foundation of effective stem cell‐derived tissue engineering. Here, the key concepts of cardiac development that are successfully applied in a bioinspired approach to growing engineered cardiac tissues, are reviewed. The native cardiac milieu is studied extensively from embryonic to adult phenotypes, as it provides a resource of factors, mechanisms, and protocols to consider when working toward establishing living tissues in vitro. It begins with the various cell types that constitute the cardiac tissue. It is discussed how myocytes interact with other cell types and their microenvironment and how they change over time from the embryonic to the adult states, with a view on how such changes affect the tissue function and may be used in engineered tissue models. Key embryonic signaling pathways that have been leveraged in the design of culture media and differentiation protocols are presented. The cellular microenvironment, from extracellular matrix chemical and physical properties, to the dynamic mechanical and electrical forces that are exerted on tissues is explored. It is shown that how such microenvironmental factors can inform the design of biomaterials, scaffolds, stimulation bioreactors, and maturation readouts, and suggest considerations for ongoing biomimetic advancement of engineered cardiac tissues and regeneration strategies for the future. Abstract : This paper provides a review of key concepts of cardiac development and suggests strategies for harnessing them in a biomimetic approach to growing engineered cardiac tissues. The origin and ideal cellular components of the myocardium are discussed. Embryonic signaling pathways that have been leveraged in the design of culture media, differentiation protocols, and electromechanical stimulation bioreactors are presented.